Dung beetles (coleoptera: scarabaeoidea) from Tasik Chini biosphere reserve, Pahang - Aruchunnan G.,; Ng, Yong Foo; Izfa Riza Hazmi,; Wee, Suk Ling (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
A total of 15,747 dung beetles belong to 13 genera and 60 species were captured successfully at Tasik Chini Biosphere Reserve, Pahang from May 2014 to April 2015. Forty-five baited pitfall trap with light sources were installed using transects method at core, buffer and transition zones of Biosphere Reserve. Onthophagus with 43 species (71.7% of the total species) represents the most diverse dung beetle genus at Tasik Chini, Pahang. The most abundant dung beetle species in the area was Sisyphus thoracicus, represented by 9,544 (60.6%) individuals. Followed by O. crassicollis and O. rorarius, which were represented by 1,041 and 9,49 individuals respectively. The Biosphere Reserve is also categorized by the occurrence of rare dung beetle species such as Onthophagus sp. 1, O. avocetta, O. namnaoensis, O. semiperakensis, Ochicanthon okudai and Copris haroldi. The list presented with 60 species of Tasik Chini dung beetles could serve as baseline data for further studies on dung beetle diversity in Peninsular Malaysia.